Predicting Posttraumatic Growth among Firefighters: The Role of Deliberate Rumination and Problem-Focused Coping - Yang, Seung-Kyoung (Int J Environ Res Public Health, 2019)
Exposure to work-related traumatic incidents in firefighters may result in positive psychological changes which are termed “posttraumatic growth”. This study aimed to construct structure equation modeling based on the model of posttraumatic growth in firefighters. Methods: A total of 226 firefighters who had experienced a work-related traumatic incident participated. The participants from three municipal fire departments and seven fire stations completed an anonymous survey asking about extraversion, optimism, calling in the workplace, problem-focused coping, deliberate rumination, and posttraumatic growth. The model fit indices were suitable for the recommended level. Seven of the 11 paths established in the initial hypothetical model were identified. The variables of deliberate rumination, problem-focused coping, and extraversion had a significant effect on the posttraumatic growth of firefighters, with an explanatory power of 38.7%. The findings show that it is important to develop strategies to enhance deliberate rumination and problem-focused coping for firefighters after work-related traumatic events.